Exploring staff involvement in an organization development intervention in a school in the Kavango region, Namibia: a case study - Rengura, Demetrius Kativa (Rhodes University, Faculty of Education, Department of Education, 2012)
Since independence, the Namibian education system has experienced a process of transformation from authoritarianism to democratisation. The philosophy underpinning this process is spelt out in the policy, Toward Education for All, with its four major goals being: Access, Equity, Quality and Democracy. Democratisation of education would mean that people would be equally involved in decision" making processes both at the system and organizational level, so as to contribute collectively to shaping the destiny of education in Namibia. This would mean at the school level of an organization, that teachers are the facilitators of democracy and agents of change in the learning organization environment. To strengthen democracy and empower people's participation in the decision" making process, Namibia further adopted a decentralization policy which involved the devolution of power and administrative functions from central government to regional authorities. In the context of this policy framework, schools should take responsibility to introduce and manage change in their organizations. However, evidence suggests that schools have been slow to take up the challenge and that change is largely still initiated by regional officials. This study looks at how organisation development (OD) may play a role in encouraging a mindset where change may be initiated by the organisation itself. OD is a planned change strategy based on normative re" educative and empirical rational strategies implemented systematically. OD is participant driven, involving a series of activities that move the organization to a preferred future. It focuses on human behaviour and organizational change through staff participation practising a bottom" up rather than top" down approach. This study reports on an OD intervention in a rural school east of Rundu, in the Kavango Educational region of Namibia. The study aimed at exploring staff involvement in an OD intervention and probed participants' perceptions and experiences of the process. The study is an action research case study located within the interpretive and critical paradigms. Observation and semi" structured interviews were the main data" collection tools used in the study. In its preliminary investigation the study found that a lack of staff involvement in decisionmaking processes and participation in meetings were the major factors that were perceived to retard the effectiveness of the organization. The study further found that the authoritative style of leadership in the school contributed to the lack of cooperation and participation of staff members. In contrast, the staff responded positively to the OD intervention. Participants embraced OD as a democratic approach to change as it made a meaningful impact on their understanding and conception of organization change. The intervention further empowered participants with new skills and knowledge of initiating change and problem" solving. Apart from that, the intervention provided a possible short" term outcome that encouraged participants to adopt and apply OD in the future, without underestimating the difficulties associated with the process.
Keywords: Education -- Namibia -- Kavango; Educational change -- Namibia -- Kavango; Organizational change -- Namibia -- Kavango; School management and organization -- Namibia -- Kavango; School improvement programs -- Namibia -- Kavango; Management -- Employee participation -- Namibia -- Kavango; Action research in education -- Namibia -- Kavango